Accumulation of Chrom (Cr) Contaminant in Rice Plant Around The Area Opak River Flow, Bantul Regency: AKUMULASI PENCEMAR KROMIUM (Cr) PADA TANAMAN PADI DI SEPANJANG KAWASAN ALIRAN SUNGAI OPAK, KABUPATEN BANTUL - Laoli, Boris Marselius Sevendo; Kisworo, Kisworo; Raharjo, Djoko (Biospecies, 2021)
Development of the leather tanning industry in the village of Banyakan, Piyungan, Bantul had a negative impact on the environment. The industrial waste from the leather tanning plant mixed with Cr metal enters the Opak River and is distributed to various places. River water is used as irrigation water which carries heavy metals that result in the accumulation of soil and plants, as well as another biota. The purpose of this study was to determine the profile and level of chromium accumulation in plants along the Opak River. The study was conducted at 6 stations in 6 different districts consisting of samples of irrigation water, sediment, stem roots, leaves, and rice plants. Heavy metal analysis on the sample was carried out using the AAS (Atomic Absorption Spectrophotometry) method. The results of the analysis of heavy metal concentrations that are distributed to the environment show that the plants that are the highest are 2,470 ppm, then sediment is 1,161 ppm, and irrigation water is 0.235 ppm. The highest accumulation of heavy metal Cr in the planting section of rice was consecutively in the grain > leaves > roots > stems. Results of the analysis of the BCF value of rice plant were categorized as a moderate accumulator plant, while the analysis of the TF value of rice plant was categorized as a phytoextraction plant. Health risk analysis HQ > 1, which means that rice from all stations is hazardous to health. Rice and water samples exceeded the established quality standard threshold, except for sediment which was still at a critical level.